2023
DOI: 10.31234/osf.io/m4u5j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relation of Representational Competence and Conceptual Knowledge in Female and Male Undergraduates

Abstract: BackgroundRepresentational competence is commonly considered to be a prerequisite for the acquisition of conceptual knowledge, yet little exploration has been undertaken into the relation between these two constructs. Using an assessment of representational competence with vector fields that functions without confounding topical context, we examined its relation with N = 515 undergraduates’ conceptual knowledge about electromagnetism.ResultsApplying latent variable modeling, we found that students’ representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…In addition, the authors found that in a scatter plot, there were almost no students with high conceptual knowledge but low representational competence, whereas there appeared to be more students with high representational competence but low conceptual knowledge (see Figure 1). From these results, the authors inferred the hypothesis that representational competence is a necessary yet insufficient prerequisite for developing conceptual knowledge (Edelsbrunner et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…In addition, the authors found that in a scatter plot, there were almost no students with high conceptual knowledge but low representational competence, whereas there appeared to be more students with high representational competence but low conceptual knowledge (see Figure 1). From these results, the authors inferred the hypothesis that representational competence is a necessary yet insufficient prerequisite for developing conceptual knowledge (Edelsbrunner et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, we are concerned with the empirical relationship between representational competence and conceptual knowledge and, in particular, with the conditions that might influence the magnitude of this relationship. Although a strong positive relationship has been assumed by many researchers, it has been noted that the quantitative empirical evidence on this relationship is rather sparse and struggles with methodological issues (Chang, 2018;Edelsbrunner et al, 2022). As Edelsbrunner et al (2022) note, instruments that have been used to measure these two constructs and their interrelations often have not been psychometrically validated, or suffer from contextual bias.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations